INNOVATIONAL CONSTITUENT OF MONOPOLISM UNDER THE CONDITIONS OF ECONOMIC GLOBALIZATION - V. Vaks (Russian Journal of Economics and Law)
The article analyses the issues of compatibility of innovation activity and monopolism at the global level. The author marks the special role of innovation activity under the conditions of globalizing markets and researches the interaction of innovation and monopoly relations at global level, which leads to the conclusions referring to the market structures created by such interaction.